Financial Feasibility Analysis Of Touch Processing Business In Wulanga Village, West Muna Regency (Case Study: Al Fatah Home Industry) - Erni Purnawati; La Karimuna; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to analyze the financial feasibility of the Al Fatah tofu processing business in Wulanga Jaya Village, West Muna Regency, and determine the sensitivity level of the financial feasibility of Al Fatah tofu processing business in Wulanga Jaya Village, West Muna Regency. Respondents were taken in this study as many as three people, namely one leader and two employees of the production division. The data analysis method used in this research uses the cost, income, and profit analysis formula. Meanwhile, to calculate business feasibility, the formulas used are Revenue Cost Ratio (R/C), Break Even Point (BEP), and Return On Investment (ROI). The results showed that the average profit received by the Al Fatah tofu processing business artisans was Rp. 74,669,880/year. Based on the calculation of business feasibility obtained R/C 4.06, production BEP value of 3,244 kg, BEP price of Rp. 184.31 and an ROI value of 30.69%, so the al Fatah tofu processing business in Wulanga Jaya Village, West Muna Regency, is feasible.